Echocardiographic evaluation of velocity ratio, velocity time integral ratio, and pulmonary valve area in dogs with pulmonary valve stenosis. (5th August 2018) - Nishimura, Satoko; Visser, Lance C.; Bélanger, Catherine; Oldach, Maureen S.; Gunther‐Harrington, Catherine T.; Stern, Joshua A.
Abstract : Background: Velocity ratio, velocity time integral (VTI) ratio, and pulmonary valve area indexed to body surface area (iPVA) are methods of assessment of pulmonary valve stenosis (PS) severity that are less dependent on blood flow. Studies evaluating these methods are limited. Objectives: To determine the effects of butorphanol, atenolol, and balloon valvuloplasty (BV) on velocity ratio, VTI ratio, iPVA, mean PG, and max PG. Animals: Twenty‐seven dogs with PS (max PG >50 mm Hg). Methods: Prospective study. All dogs underwent an echocardiogram at baseline, 5‐minutes after administration of butorphanol (0.2‐0.25 mg/kg IV), and 2‐to‐4 weeks after atenolol (1‐1.5 mg/kg q12h). Twenty‐one of these were evaluated 24‐hours after BV. Results: There were no significant differences ( P > .05) amongst any of the methods of assessment of PS severity after butorphanol. After atenolol, mean (SD) of mean (57.0 [21.0] mm Hg) and max PG (93.1 [33.8] mm Hg) were significantly decreased ( P ≤ .047) compared with baseline (65.2 [26.2] mm Hg and 108 [44.4] mm Hg, respectively). After atenolol, there were no significant ( P ≥ .12) differences in velocity ratio (0.29 [0.09]), VTI ratio (0.18 [0.05]), or iPVA (0.43 [0.16] cm 2 /m 2 ) compared with baseline (0.30 [0.09], 0.19 [0.09], 0.44 [0.17] cm 2 /m 2, respectively). Conclusions and Clinical Importance: Atenolol might reduce mean and max PG but does not alter less flow‐dependent methods of assessment of PS severity (velocity ratio, VTI ratio, and iPVA) in dogs with PS. Results support an integrative approach to assessment of PS severity that includes less flow‐dependent methods, particularly in states of altered flow or right ventricular function.